(untitled) (Modern education and development, 2024)
Conveying meaning from one language to another is the process of translation. In order to meet language, cultural, and contextual barriers, it encompasses a variety of forms and tactics. Equivalence is a key idea in translation theory that aims to strike a balance between target audience comprehension and faithfulness to the original text. The main categories of translation and the equivalency principle are examined in this article, with a focus on their significance in maintaining cultural context and meaning.